Digital collections and exhibits - Denzer, Juan, 1972- (Library technology essentials ;, 2015)
Today's libraries are taking advantage of cutting-edge technologies such as flat panel displays using touch, sound, and hands-free motions to design amazing exhibits using everything from simple computer hardware to advanced technologies such as the Microsoft Kinect. Libraries of all types are striving to add new interactive experiences for their patrons through exciting digital exhibits, both online and off. Digital Collections and Exhibits takes away the mystery of designing stunning digital exhibits to spotlight library treasures by walking the reader through implementation projects that are sure to astound and impress. This collection of easy-to-follow instructions will give readers the knowledge and confidence to create and design their very own extraordinary digital exhibits. Readers will learn: How to Create a Digital Exhibit Using Omeka.net How to Create a Hands-Free Digital Exhibit Showcase with Microsoft Kinect How to Create a Digital Exhibit Using Open Exhibits How to Create 3D Objects and Add them to Online Exhibits.